2023
DOI: 10.1186/s13071-022-05581-4
|View full text |Cite
|
Sign up to set email alerts
|

The pipeline for drugs for control and elimination of neglected tropical diseases: 1. Anti-infective drugs for regulatory registration

Abstract: The World Health Organization ‘Ending the neglect to attain the Sustainable Development Goals: A road map for neglected tropical diseases 2021–2030’ outlines the targets for control and elimination of neglected tropical diseases (NTDs). New drugs are needed to achieve some of them. We are providing an overview of the pipeline for new anti-infective drugs for regulatory registration and steps to effective use for NTD control and elimination. Considering drugs approved for an NTD by at least one stringent regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 109 publications
0
41
0
Order By: Relevance
“…The FDPS inhibitors include alendronate 56 , incadronate (INC, also named cimadronate or YM-175) 56 , 57 , ibandronate 56 , 58 , 59 , minodronate 56 , risedronate 56 , pamidronate 56 , zoledronate 56 . The CYP51 inhibitors include albaconazole (also named stiefel or UR-9825) 60 , 61 , arasertaconazole nitrate 62 , 63 , Bifonazole (also named B3LYP) 64 - 67 , butoconazole (BTZ) 68 , 69 , clotrimazole 70 , dapaconazole 71 , 72 , eberconazole (EBZ) 73 , econazole (also named EcoNai™, SEPA, Spectazole, Ecostatin, or Pevaryl) 74 , 75 , efinaconazole (also named KP-103 or Jublia) 41 , 76 , 77 , fluconazole 78 , flutrimazole 79 , 80 , fosravuconazole (F-RVCZ, the prodrug of ravuconazole (also named E1224)) 81 - 86 , genaconazole (also named SCH 39304, a racemic mixture that contains 50% of the SCH 42427 and 50% of SCH 42426 enantiomers) 87 , 88 , HCP002 (a phosphate-modified derivative of voriconazole) 89 , IDP113 90 , isavuconazole (ISA, the prodrug of isavuconazole (BAL 4815)) 91 , 92 , ketoconazole (KTC) 93 - 95 , levoketoconazole 95 , 96 , itraconazole 97 , luliconazole 85 , 98 , miconazole 99 , opelconazole (also named PC945) 100 , 101 , oteseconazole (also named VT-1161) 102 , posaconazole 84 , 103 , pramiconazole (also named R126638) 104 - 107 , quilseconazole (also named VT-1129) 108 , 109 , SSY726 110 , 111 , voriconazole ...…”
Section: The Potential Of Cholesterol Synthesis Genes In Drug Develop...mentioning
confidence: 99%
“…The FDPS inhibitors include alendronate 56 , incadronate (INC, also named cimadronate or YM-175) 56 , 57 , ibandronate 56 , 58 , 59 , minodronate 56 , risedronate 56 , pamidronate 56 , zoledronate 56 . The CYP51 inhibitors include albaconazole (also named stiefel or UR-9825) 60 , 61 , arasertaconazole nitrate 62 , 63 , Bifonazole (also named B3LYP) 64 - 67 , butoconazole (BTZ) 68 , 69 , clotrimazole 70 , dapaconazole 71 , 72 , eberconazole (EBZ) 73 , econazole (also named EcoNai™, SEPA, Spectazole, Ecostatin, or Pevaryl) 74 , 75 , efinaconazole (also named KP-103 or Jublia) 41 , 76 , 77 , fluconazole 78 , flutrimazole 79 , 80 , fosravuconazole (F-RVCZ, the prodrug of ravuconazole (also named E1224)) 81 - 86 , genaconazole (also named SCH 39304, a racemic mixture that contains 50% of the SCH 42427 and 50% of SCH 42426 enantiomers) 87 , 88 , HCP002 (a phosphate-modified derivative of voriconazole) 89 , IDP113 90 , isavuconazole (ISA, the prodrug of isavuconazole (BAL 4815)) 91 , 92 , ketoconazole (KTC) 93 - 95 , levoketoconazole 95 , 96 , itraconazole 97 , luliconazole 85 , 98 , miconazole 99 , opelconazole (also named PC945) 100 , 101 , oteseconazole (also named VT-1161) 102 , posaconazole 84 , 103 , pramiconazole (also named R126638) 104 - 107 , quilseconazole (also named VT-1129) 108 , 109 , SSY726 110 , 111 , voriconazole ...…”
Section: The Potential Of Cholesterol Synthesis Genes In Drug Develop...mentioning
confidence: 99%
“…We have previously provided an overview of new small-molecule anti-infective molecular entities (drugs) in the pipeline for NTD control and elimination strategies which have recently been approved by a regulatory authority for treatment of an NTD or are in at least Phase 2 clinical development for regulatory approval for an NTD [ 2 ]. Research and development (R&D) of new drugs comes with a significant risk of failure and it takes many years even from initiation of Phase 2 clinical development to the first regulatory agency approval (registration).…”
Section: Introductionmentioning
confidence: 99%
“…R&D for new drugs also requires significant financial resources to achieve regulatory registration and further resources to maintain the registration [ 3 ]. Furthermore, studies beyond those that supported regulatory approval may be needed to provide the basis for inclusion of the new drug in WHO guidelines, country policies and practice [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, an international consultation concluded that parasite elimination through MDAi was feasible in the six Central and South American countries of the Americas (total population at risk around 0.56 million), but not across the vast and partly hyperendemic areas in Sub-Saharan Africa [8], requiring research for new drugs or drug combinations [9,10]. Since then, onchocerciasis has been eliminated in the Americas in all but the large endemic area crossing the Venezuela-Brazil border.…”
Section: Introductionmentioning
confidence: 99%
“…Potential strategies identi ed include those based on moxidectin which was approved in 2018 for treatment of O. volvulus infected individuals ≥ 12 years of age by the US Food and Drug Administration (FDA) [19,20,21,22,23,24,25,26,27]. Discovery, development and implementation research for other ATS [28] is also ongoing including for new or repurposed drugs [10,29,30,31,32], for effective, affordable, and sustainable complementary vector control strategies [33,34] and for approaches to safe use of ivermectin in loiasis coendemic areas (drugs for safe reduction of Loa loa micro laraemia [35,36,37] and 'test-and-not-treat' or 'test-and-treat' strategies [38,39,40,41,42]). Furthermore, research for a vaccine is continuing [43].…”
Section: Introductionmentioning
confidence: 99%